MENINGKATKAN KETERAMPILAN MENULIS DENGAN MENERAPKAN METODE TEAM ACCELERATED INSTRUCTION (TAI) DALAM MENULIS PENGUMUMAN - Sahleni, Sahleni; Djuanda, Dadan; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
Learning to write announcements based on the theme in grade IV SDN Gudangkopi I experienced problems. Therefore, researchers chose the method of Team Accelerated Instruction (TAI) as a solution. In this research use Kemmis and Taggart Class Action Research (PTK) design. The instruments used are observation guides, interview guides, field notes and evaluation questions. Validation of data used is member check, triangulation, and expert opinion. Based on the results of research, teacher performance planning increased every cycle that is, the cycle I 88.89%, 92.59% II cycle, and 100% III cycle. Implementation of teacher performance has increased that is cycle I 58,59%, cycle II 97,44%, and cycle III 100%. Assessment of student activity increased in cycle I 7,69%, cycle II 30,77%, and cycle III 88,46%. The learning results of writing skills are also increasing. In the first cycle students complete 6 people (23.07%), cycle II 16 students complete (61.54%), and cycle III students complete 23 people (88.46%). Thus proving that the Team Accelerated Instruction (TAI) method can improve the writing skills of announcement by theme.